Two-photon-absorption in semiconductor micro-cavities - Krug, Torsten (Trinity College (Dublin, Ireland). School of Physics, 2006)
In this thesis a study of two-photon absorption photoconductivity in semiconductor microcavities is presented. It can be shown that a 10,000-fold enhancement of the non-linear two-photon absorption response can be obtained with the microcavity structure. In this thesis the detail of the design and performance (dynamic range, speed, bandwidth) of such devices will be discussed. Two examples are studied, an AlGaAs/GaAs microcavity working at 890 nm and a GaAs/AlAs structure working at 1.55 μm. These devices can potentially be used for low intensity, fast autocorrelation and demultiplexing applications in optical-communication networks.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin